(untitled) (Research, Society and Development, 2023)
The increase in the consumption of dietary supplements is noticeable, especially protein-based products. Among them, Whey Protein stands out, a protein extracted from whey, available on the market by several brands with different characteristics. Proper labeling of these supplements is a consumer’s right and optimizes their choice. The objective is to analyze the labeling of national protein supplements based on Whey Protein. This is a quantitative and exploratory research, involving evaluation of the labeling of different brands of Whey Protein. The study sample consisted of 6 brands of protein supplements of the Whey Protein Blend type, with whey as the only protein source, available on the national market. A checklist was prepared in the Microsoft Excel program in accordance with the items of current legislation. Two types of materials referring to the packaging of the analyzed products were identified, high density polyethylene and polyethylene terephthalate. All brands presented a meter and method of preparation. They differed in terms of the amount of protein offered per dose. Among the evaluated brands, 83.33% present at least one type of non-compliance, with emphasis on RDC nº 18 of 2010, which presented the highest number of inadequacies. The results point to the need for continuous inspection of the labels, mainly regarding the mandatory specifications of current legislation. It highlights the need and intensification of continuous and effective inspection of product labels, to guarantee consumers access to reliable information and help in their choices at the time of purchase.